Taste Disorder and Tongue Numbness After Lithium Overdose - Si-Yu Chu; Huang-Chi Wang; Ming-Hong Hsieh; Cheng-Chen Chang (Acta Neurologica Taiwanica)
Purpose: Drug-induced taste disturbances are prevalent in clinical practice, with dysgeusia being a frequent manifestation. This study aims to present a case of taste disorders and tongue numbness induced by a lithium overdose. Case Report: A 33-year-old woman with bipolar II disorder attempted suicide by ingesting multiple drugs, including lithium and benzodiazepines. She exhibited weakness but was conscious after admission. Laboratory analyses indicated elevated serum lithium and urine benzodiazepine levels. Admitted to a psychiatric ward, her symptoms included diarrhea, poor appetite, and postprandial nausea. Two weeks later, she reported altered taste sensations and tongue numbness following the overdose. Her ongoing medication included venlafaxine, valproate sodium, and clozapine. Symptoms improved over time without specific treatment, aligning with increased appetite and weight gain. Conclusion: Drug-induced taste disturbances have a substantial impact on patients’ quality of life and medication adherence. This case brings attention to taste disorders induced by lithium and suggests potential mechanisms that could contribute to taste alterations. It underscores the importance of conducting thorough assessments in patients experiencing gustatory symptoms, particularly during the ongoing pandemic.